PENGEMBANGAN SISTEM INFORMASI PENJEMPUTAN SAMPAH MENGGUNAKAN GLOBAL POSITIONING SYSTEM (GPS) BERBASIS ANDROID DI YOGYAKARTA - Arya Fito Pramanda (The Indonesian Journal of Computer Science Research, 2023)
GPS technology is a satellite-based navigation technology with more than 30 satellites orbiting 20,000 km above the earth's surface. GPS is widely used for various purposes, such as directions and determining the location point of a place. In this study using GPS technology to determine the location of garbage pickup. Garbage is a common problem in most countries, including Indonesia. Garbage is a source of disease if left alone. Limited access to landfills makes people only throw garbage in certain places that are not actually landfills. The location of the garbage is unknown to the janitor and if left unchecked, there will be a buildup of garbage. The use of geocoding technology in the Global Positioning System (GPS) can make it easier for people to call cleaners by providing the location of garbage collection sites that were previously unknown to cleaners. To attract people to use this application, there are points earned after collecting garbage. These points can be exchanged into credit, E-Wallet balance, or retail vouchers. With this application, garbage that accumulates in places that were previously difficult to reach by cleaners can be handled faster.